The Impact of Armed Conflict on the Prevalence and Transmission Dynamics of HIV Infection in Libya - Daw, Mohamed Ali; El-Bouzedi, Abdallah Hussean; Ahmed, Mohamed Omar (Frontiers in Public Health, 2022)
The interrelationships between HIV/AIDS and armed conflict are a complex phenomenon, and studies are rarely devoted to this area of research. Libya is the second-largest country in Africa that has been evoked with war since the NATO intervention in 2011. The country has also experienced one of the largest HIV outbreaks associated with the Bulgarian nurse's saga. The effect of the armed conflict on the dynamic spread of HIV is not yet well-known. The objectives of this study were to determine the impact of armed conflict on the epidemiological situation of HIV infection in Libya and to analyze the transmission dynamics of HIV strains during the conflict. We investigated the movement of people with HIV during the Libyan armed conflict, analyzed the HIV subtypes reported from 2011 to 2020, and followed up the infected cases all over the country. The patterns of HIV spread within the Libyan regions were traced, and the risk factors were determined during the conflict period. A total of 4,539 patients with HIV/AIDS were studied from the four regions during the Libyan conflict. Our data analysis indicated that Benghazi, the biggest city in the Eastern region, was the significant exporter of the virus to the rest of the country. The viral dissemination changes were observed within the country, particularly after 2015. A major virus flows from the Eastern region during the armed conflict associated with internally displaced people. This resulted in the dissemination of new HIV strains and accumulations of HIV cases in western and middle regions. Although, there were no significant changes in the national prevalence of HIV/AIDS. Our data highlight the factors that complicated the spread and dissemination of HIV during the armed conflict, which provide a better understanding of the interaction between them. This could be used to plan for effective preventive measures in tackling the spread of HIV in conflict and post-conflict settings.